Alpha-Synuclein Levels in Blood Plasma Decline with Healthy Aging - Koehler, Niklas K. U. (2015)
There is unequivocal evidence that alpha-synuclein plays a pivotal pathophysiological role in neurodegenerative diseases, and in particular in synucleinopathies. These disorders present with a variable extent of cognitive impairment and alpha-synuclein is being explored as a biomarker in CSF, blood serum and plasma. Considering key events of aging that include proteostasis, alpha-synuclein may not only be useful as a marker for differential diagnosis but also for aging per se. To explore this hypothesis, we developed a highly specific ELISA to measure alpha-synuclein. In healthy males plasma alpha-synuclein levels correlated strongly with age, revealing much lower concentrations in older (avg. 58.1 years) compared to younger (avg. 27.6 years) individuals. This difference between the age groups was enhanced after acidification of the plasmas (p<0.0001), possibly reflecting a decrease of alpha-synuclein-antibody complexes or chaperone activity in older individuals. Our results support the concept that alpha-synuclein homeostasis may be impaired early on, possibly due to disturbance of the proteostasis network, a key component of healthy aging. Thus, alpha-synuclein may be a novel biomarker of aging, a factor that should be considered when analyzing its presence in biological specimens.